Ion-Exchange-Induced Transformation and Mechanism of Cooperative Crystal Chemical Adaptation in Sitinakite: Theoretical and Experimental Study - Taras L. Panikorovskii; Galina O. Kalashnikova; Anatoly I. Nikolaev; Igor A. Perovskiy; Ayya V. Bazai; Victor N. Yakovenchuk; Vladimir N. Bocharov; Natalya A. Kabanova; Sergey V. Krivovichev (Minerals, 2022)
The microporous titanosilicate sitinakite, KNa2Ti4(SiO4)2O5(OH)·4H2O, was first discovered in the Khibiny alkaline massif. This material is also known as IONSIV IE-911 and is considered as one of the most effective sorbents for Cs+ and Sr2+ from water solutions. We investigate a mechanism of cooperative crystal chemical adaptation caused by the incorporation of La3+ ions into sitinakite structure by the combination of theoretical (geometrical–topological analysis, Voronoi migration map calculation, structural complexity calculation) and empirical methods (PXRD, SCXRD, Raman spectroscopy, scanning electron microscopy). The natural crystals of sitinakite (a = 7.8159(2), c = 12.0167(3) Å) were kept in a 1M solution of La(NO3)3 for 24 h. The ordering of La3+ cations in the channels of the ion-exchanged form La3+Ti4(SiO4)2O5(OH)·4H2O (a = 11.0339(10), b = 11.0598(8), c = 11.8430(7) Å), results in the symmetry breaking according to the group–subgroup relation P42/mcm → Cmmm.